The Politico-Strategic Dimension of the US Proposal for a Free Trade Agreement with the Philippines - Renato Cruz de Castro (Philippine Institute for Development Studies (PIDS), 2006)
This research paper examines the politico-strategic motivations of the Bush Administrations effort to foster Free Trade Agreements to a number of countries, including the Philippines. It argues that FTAs are being used by the U.S. as means of advancing the trade interest of American business, as well as ensuring its leadership in the global political economy. The article observes that the current attempt of the Bush Administration to push for FTAs is driven by political dynamics. Among these are the competition between the Congress and the White House, the U.S. strategy in the war on terror, pressuring the E.U to another round of trade liberalization negotiations, and ensuring American access to the East Asian regional economy. The article then discusses the specific politico-strategic motives of the Bush Administration in its offer of an FTA to the Philippines. In conclusion, it explores the possible political ramifications of an FTA with the U.S. on Philippine society and how the Philippine government can respond to this offer of a preferential trading arrangement from its major security ally.
Keywords: 330; East Asia FTA; preferential trading arrangements (PTAs); competitive trade liberalization; American economic hegemony; war on terror; Trade Promotion Authority Act; Trade Negotiating Authority of 2001; Philippine foreign policy; Internationale Wirtschaftsbeziehungen; Freihandelszone; Handelsliberalisierung; Außenwirtschaftspolitik; Philippinen; USA